Contingent valuation of a haze adaptive program : a study on the 2015 transboundary haze in Malaysia - Tan, Brandon Tao Wei (2019)
The 2015 Indonesian transboundary haze episode caused adverse impacts in terms of economy and citizens’ health across many Southeast Asian countries. In Malaysia, while regional and local haze adaptive measures have been employed consistently, non-market costs of haze have yet to be explored in great length by academics. In this study, a Contingent Valuation (CV) survey was designed with two-fold objectives. Firstly, this paper aims to elicit Malaysians’ willingness-to-pay (WTP) for a haze adaptive program using a Double Bounded Dichotomous Choice Contingent Valuation survey. Secondly, this paper aims to examine how Knowledge, Attitudes and Practices (KAP), as well as Malaysians’ concern for the environment affect Malaysians’ WTP for a haze adaptive program. A set of questions on Knowledge, Attitudes and Practices (KAP) was included in the survey to examine key contributing factors to WTP beyond the usual control variables. Additionally, this paper also examined how concern for the environment affects WTP. These objectives were analyzed using data collected from a total of 900 face-to-face surveys administered in shopping malls and offices across Malaysia. A double-bounded probit model was then used to analyze responses of the CV questionnaire and to identify statistically significant variables of interest that influence WTP. This paper found that the aggregate WTP for Malaysians on a haze adaptive program is approximately RM6.84 billion, which is 0.56% of the real inflation-adjusted GDP in 2018. Our analysis revealed that WTP is positively influenced by knowledge on haze, attitudes towards haze, environmental concern as well as high environmental rating, positive forecast, having a child, large household size and having family history of breathing problems. We also found that Malaysians have basic knowledge on haze and mildly optimistic attitudes towards haze. However, in general, they are found to have poor haze practices despite a strong environmental concern. With greater understanding of the determinants that elicit greater contributions from its citizens, education policies can target improvement on general knowledge and attitudes on haze. Greater WTP values can also be potentially elicited from citizens who are less sensitive to pollutant air, i.e. those providing good air quality ratings when actual ratings are poor. Relevant agencies can target them by utilizing the framing effect from the perspective of benefitting the health of their loved ones, as well as the portrayal of poor air quality through facts.